Software for longitudinal and integrated analysis of physical capacities of individuals and groups of athletes - Barreira Augusto, J.; Vaz Macedo, D.; Brenzikofer, R. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study is to present the Athlete Profile software which was developed to assist professionals involved in sport training to extract information from results of physical tests carried out by large groups of athletes. Through different graphic resources the software allows, in an interactive way, the simultaneous viewing of the performance of an athlete in all physical tests at different moments of training and the comparison with the evolution of his group. Using reference tables that classify the results of each test from very low to excelent, depending on the sex and age of the athlete, the software also allows the physical fitness characterization and the comparison of the physical development of the athlete with the expected.